The international education experience: identity formation and audibility through participation, adjustment, and resistance. Issue 4 (3rd July 2020) - Matsunaga, Kaoru; Chowdhury, Raqib; Barnes, Melissa Marie; Saito, Eisuke
ABSTRACT: For international students undertaking higher education in English-speaking countries, often social and academic competencies are at odds with the expectations of the classroom discourse communities and the normative behaviours and practices of these communities. This conceptual paper argues that despite some scholarly studies seeing such international experience as a process of adjustment in a one-way transmissive exchange, international students often activate their agency to recognise the nature of normative behaviours and classroom practices, align themselves to these, and when necessary resist or use affordances to empower themselves and become legitimate members of their classroom communities. International education, thus, shapes international students' identities through not just their conformity to institutional expectations, but crucially to their responses to the practices, challenges, and opportunities for empowerment, and continuous self-realisation of their current view of their selves and the desired outcome of their selves.